Functional pomegranate beverage production by fermentation with a novel synbiotic L. paracasei biocatalyst. (5th March 2020) - Mantzourani, Ioanna; Terpou, Antonia; Bekatorou, Argyro; Mallouchos, Athanasios; Alexopoulos, Athanasios; Kimbaris, Athanasios; Bezirtzoglou, Eugenia; Koutinas, Athanasios A.; Plessas, Stavros
Highlights: Novel probiotic L. paracasei strain was immobilized on delignified wheat bran. The immobilized biocatalyst was efficient for pomegranate juice fermentation. Total phenolic content and aroma volatiles were increased after fermentation. Immobilization enhanced cell viability above levels required for probiotics. Good quality, potentially synbiotic, pomegranate beverages can be produced. Abstract: The recently isolated Lactobacillus paracasei K5 (a potential probiotic) was immobilized on delignified wheat bran (DWB) and was used to produce a functional pomegranate beverage. Fermentations were carried out for 24 h at different pH values (3.3, 3.6, and 3.9), and the fermented juices were stored for 4 weeks at 4 °C. In all cases, the immobilized biocatalyst was shown to be efficient for pomegranate juice fermentation, as indicated by analysis of sugars and organic acids, and ethanol production was maintained at low levels (0.5–1% v/v). The sugars consumed during fermentation were used mainly for cell mass production, while DWB exerted a prebiotic effect, protecting and enhancing the viability of L. paracasei . Optimum viability (9.8–11.7 log cfu/mL) was achieved at pH 3.9. The phenolic content and headspace volatiles were increased after fermentation and storage (112 ± 17–213 ± 30 mg GAE/100 mL and 27–46 compounds, respectively), indicating potential to produce good quality, synbiotic pomegranate beverages.